2008
DOI: 10.1111/j.1365-2672.2007.03669.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of detection medium for hard-to-culture beer-spoilage lactic acid bacteria

Abstract: Aims:  To develop a detection medium for hard‐to‐culture beer‐spoilage lactic acid bacteria (LAB). Methods and Results:  Four hard‐to‐culture beer‐spoilage strains of LAB, belonging to Lactobacillus paracollinoides and Lactobacillus lindneri, have been obtained by repeatedly subculturing the wild‐type strains in beer. To develop a countermeasure against these hard‐to‐culture beer‐spoilage LAB, a beer‐based medium was modified. As a consequence, the supplementation of a small amount of de Man Rogosa Sharpe medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
3

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 31 publications
(62 reference statements)
3
48
0
3
Order By: Relevance
“…It has been increasingly recognized that microorganisms too deeply associated with a particular environment tend to exhibit hard-to-cultivate characteristics 50,56 . These lines of evidence therefore suggest the profound association of these species with beer brewing environments and indicate that the physiological characteristics of beer spoilage LAB living in beer brewing environments are drastically different from those of laboratory strains maintained in nutrient-rich media 103 . It should be also noted that, due to the hard-to-cultivate nature of L. lindneri, L. paracollinoides and P. damnosus, these LAB species may have been underreported as causative agents of microbiological incidents in the beer brewing industry.…”
Section: Association Of Beer Spoilage Lab With Their Habitatmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been increasingly recognized that microorganisms too deeply associated with a particular environment tend to exhibit hard-to-cultivate characteristics 50,56 . These lines of evidence therefore suggest the profound association of these species with beer brewing environments and indicate that the physiological characteristics of beer spoilage LAB living in beer brewing environments are drastically different from those of laboratory strains maintained in nutrient-rich media 103 . It should be also noted that, due to the hard-to-cultivate nature of L. lindneri, L. paracollinoides and P. damnosus, these LAB species may have been underreported as causative agents of microbiological incidents in the beer brewing industry.…”
Section: Association Of Beer Spoilage Lab With Their Habitatmentioning
confidence: 98%
“…Interestingly, recent studies have shown that repeated passages in beer gradually reduce the culturability of originally easy-tocultivate strains of L. lindneri and L. paracollinoides, eventually leading to the acquisitions of hard-to-cultivate strains that mimic the state of primary isolates of these species 103,105 . Strikingly, it was observed that highly adapted strains of beer spoilage L. lindneri and L. paracol- linoides die swiftly on MRS agar (Fig.…”
Section: Association Of Beer Spoilage Lab With Their Habitatmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them the most important spoilage organisms are, according to brewing literature, L. brevis, L. lindneri, L. paracollinoides and P. damnosus 2,30,32,34 . In addition, L. backi and P. inopinatus have been reported as potential beer spoilers 7,22,33 .…”
Section: Introductionmentioning
confidence: 99%